2018
DOI: 10.1080/0284186x.2018.1487581
|View full text |Cite
|
Sign up to set email alerts
|

The survival outcome of patients with metastatic colorectal cancer based on the site of metastases and the impact of molecular markers and site of primary cancer on metastatic pattern

Abstract: Survival duration with mCRC is related to the site of metastases with lung limited disease showing a more favorable survival outcome compared to other single metastatic site disease. The BRAF mutation and primary rectal cancer were associated with poor prognostic metastatic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 43 publications
(47 reference statements)
10
69
0
3
Order By: Relevance
“…Outcomes of patients with metastatic colorectal cancer (mCRC) have improved enormously over the last decade. Indeed, depending on the extent of metastases and the biology, the median OS of metastatic colorectal cancer patients can exceed 3 years [27]. There are different factors, which led to improved outcomes in patients with metastatic colorectal cancer: first, our knowledge of the tumor heterogeneity based on molecular profiling has changed the therapeutic management of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of patients with metastatic colorectal cancer (mCRC) have improved enormously over the last decade. Indeed, depending on the extent of metastases and the biology, the median OS of metastatic colorectal cancer patients can exceed 3 years [27]. There are different factors, which led to improved outcomes in patients with metastatic colorectal cancer: first, our knowledge of the tumor heterogeneity based on molecular profiling has changed the therapeutic management of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Organ-specific susceptibility of metastasis is common in CRC and is significantly associated with primary tumor location and BRAF, KRAS, and MSI status. 38 Peritoneal metastasis is associated with increased interferon-g levels and is surrounded by natural killer (NK) cells. 37 We previously found a correlation between Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of the most common BRAF mutation in mCRC, BRAF V600E , is well characterized [129]. The survival rate of patients carrying the mutant form is decreased by approximately 50% compared to patients with wild-type BRAF (BRAF WT ) [130][131][132][133]. This is highlighted in a pooled analysis of the CAIRO, CAIRO2, COIN and Focus studies, where patients with BRAF mutations demonstrated worse median PFS and OS compared with patients that had BRAF WT tumors (PFS: 6.2 vs. 7.7 months, respectively; HR, 1.34; 95% CI, 1.17-1.54; p < 0.001; OS: 11.4 vs. 17.2 months, respectively; HR, 1.91; 95% CI, 1.66-2.19; p < 0.001) [133].…”
Section: Braf (V600e)mentioning
confidence: 99%